Mathematical Analysis, Probability and Applications - Plenary Lectures ISAAC 2015, Macau, China - Qian, Tao; Rodino, Luigi G. (Springer Proceedings in Mathematics & Statistics,, 2016)
This book collects lectures given by the plenary speakers at the 10th International ISAAC Congress, held in Macau, China in 2015. The contributions, authored by eminent specialists, present some of the most exciting recent developments in mathematical analysis, probability theory, and related applications. Topics include: partial differential equations in mathematical physics, Fourier analysis, probability and Brownian motion, numerical analysis, and reproducing kernels. The volume also presents a lecture on the visual exploration of complex functions using the domain coloring technique. Thanks to the accessible style used, readers only need a basic command of calculus.